Efficacy of Dupilumab for Atopic Dermatitis According to Clinical Course and Clinical Findings: A Multicentre Retrospective Study - Takeshi Nakahara; Makiko Kido-Nakahara; Daisuke Onozuka; Sawako Sakai; Tomoko Hirose; Nobutoshi Take; Akiko Sugiyama; Kayo Harada; Gaku Tsuji; Satoko Kikuchi; Futoshi Kohda (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)